Analysis Of Implementation Of Internal Control Of Cash Receivings And Accounts Receivables In PT. Bright M. Yamin Medan - Moudy Chairina Muchlis (TRIGIN PUBLISHER, 2021)
This research was conducted at PT. Bright Supermart M. Yamin Medan is engaged in the retail sale of products for the needs of the community. In Operational activities, companies implement internal controls to transaction cash receipts and accounts receivable. The purpose of this study to determine the effectiveness of internal control of cash receipts and accounts receivable activities to achieve the objective of operating profit. This type of research using quantitative research, while taking the measurements scale used is the scale interval. Type of research data using quantitative data and data sources using primary data and secondary data. Data collection techniques using observation and interviews. Based on the results of research conducted can be put forward that the internal control of cash receipts quite effectively obtaining a value of 82 with an internal scale of between 63-83. Meanwhile, internal controls for receivables will be considered effective obtaining a value of 84 with a scale interval between 84 -103. PT. Bright Supermart has implemented elements of internal control as well as on COSO, consisting of the control environment, risk assessment, control procedures, monitoring, and information and communications.